Move the variables to one side and the numbers to the other side.
1 - 4x = 9 - 2x
add 4x to both sides
1 = 9 +2x
subtract 9 from both sides
-8 = 2x
divide by 2 to solve
x = -4
2007-06-23 07:46:41
·
answer #1
·
answered by Wheels 3
·
0⤊
0⤋
Collect like terms first. (Put x's on the same side of the equal sign)
1-4x+4x=9-2x+4x (add 4x to both sides)
1-0x=9+2x (combined like terms, i.e. the x's)
1=9+2x
1-9=9+2x -9 (Subtract 9 from boths sides)
-8=2x (combinded like terms, i.e. the 1 and 9)
-4=x (divided both side by 2)
2007-06-23 14:53:46
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
1-4x=9-2x
1) 1=9+2x
2) -8=2x
3) -4=x
In step one, move the variables to one side of the equation.
In step two, move 9 to the other side, leaving 2x by itself.
And finally, in step 3, divide both sides by 2 and get the solution of -4.
I think this is right, not sure though. Hope this helped!
2007-06-23 14:56:59
·
answer #3
·
answered by Carley S 2
·
0⤊
0⤋
-4x+2x=9-1
-2x=8
x= -4
2007-06-23 17:32:37
·
answer #4
·
answered by Pahuni A 2
·
0⤊
0⤋
1 - 4x = 9 - 2x
1 - 9 = 4x - 2x
2x = - 8
x = - 4
2007-06-27 14:32:38
·
answer #5
·
answered by Como 7
·
0⤊
0⤋
Because you are trying to solve this problem for x the first thing you want to do when solving this problem is to bring all the x's to one side...you do this by adding (-2x) to both sides...
1-4x=9-2x (add (-2x) to both sides)
1-4x+2x=9-2x+2x(this simplifies to..)
1-2x=9
Now to solve for x we need to subract (1) from both sides...
1-2x=9(Subract (1) from both sides)
1-1-2x=9-1(this simplifies to...)
-2x=8
Now to solve for x we need to get x by it's self, so to do this you want to divide both sides by (-2)...
-2x=8(Divide both sides by (-2))
-2x/-2=8/-2(this simplifies to...)
x=-4
There you go...
2007-06-23 14:53:41
·
answer #6
·
answered by Chris 1
·
0⤊
0⤋